2020
DOI: 10.21203/rs.3.rs-32781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical ventilation of patients in helicopter emergency medical service transport: An international survey

Abstract: Background: Mechanical ventilation in helicopter emergency medical service (HEMS) environments is a procedure which carries a significant risk of complications. Limited data on the quality and performance of mechanical ventilation in HEMS are available in the literature. Method: We conducted an international survey to evaluate mechanical ventilation infrastructure in HEMS and collect data of transported ventilated patients. From June 20-22, 2019, the participating HEMS bases were asked to provide data via a we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In general, there are only few studies on the process quality of mechanical ventilation in HEMS environments (4,5,9,10). Key results of our small study sample demonstrate that participating HEMSteams were entirely physician-staffed and provided a high expertise in critical care management and long experience in HEMS.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, there are only few studies on the process quality of mechanical ventilation in HEMS environments (4,5,9,10). Key results of our small study sample demonstrate that participating HEMSteams were entirely physician-staffed and provided a high expertise in critical care management and long experience in HEMS.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies suggested that real-world handling of these high-risk patients may differ from desirable standards and often depends on the discretion of the attending HEMS team (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%